2015
DOI: 10.1080/14786419.2015.1065493
|View full text |Cite
|
Sign up to set email alerts
|

Anti-inflammatory, antioxidant and antiangiogenic activities of diosgenin isolated from traditional medicinal plant, Costus speciosus (Koen ex.Retz.) Sm

Abstract: Costus speciosus is an important medicinal plant widely used in several indigenous medicinal formulations. The present study was conducted to evaluate the in vitro anti-inflammatory, antioxidant and antiangiogenic activities of diosgenin isolated from C. speciosus. The diosgenin was isolated from C. speciosus by HPTLC and its biological activities were studied by different protocols. The results demonstrated that LPS stimulated TNF-α generation in RAW 264.7 macrophage culture supernatant up to 3.7-fold of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(17 citation statements)
references
References 9 publications
0
15
0
Order By: Relevance
“…Thus, the formation of new blood vessels in tumors actively supplies the essential nutrients and growth factors that allow tumors to acquire the ability to reject chemotherapeutic drugs and develop chemoresistance [ 27 , 65 , 66 , 67 , 68 ]. Diosgenin is also a potent inhibitor of cancer cell invasion, migration, and tumor-associated angiogenesis [ 27 , 69 ]. He et al, reported that diosgenin inhibited the invasion and migration of triple-negative breast cancer cells and was associated with the concomitant suppression of actin polymerization, phosphorylation of Vav2, and activation of Cdc42 oncoprotein expression.…”
Section: In Vitro Anti-cancer Effects Of Diosgeninmentioning
confidence: 99%
“…Thus, the formation of new blood vessels in tumors actively supplies the essential nutrients and growth factors that allow tumors to acquire the ability to reject chemotherapeutic drugs and develop chemoresistance [ 27 , 65 , 66 , 67 , 68 ]. Diosgenin is also a potent inhibitor of cancer cell invasion, migration, and tumor-associated angiogenesis [ 27 , 69 ]. He et al, reported that diosgenin inhibited the invasion and migration of triple-negative breast cancer cells and was associated with the concomitant suppression of actin polymerization, phosphorylation of Vav2, and activation of Cdc42 oncoprotein expression.…”
Section: In Vitro Anti-cancer Effects Of Diosgeninmentioning
confidence: 99%
“…In addition to functioning as a lactation aid, this bioactive substance is known for its medicinal qualities, such as antidiabetic and hypocholesterolemic effects, and can be used to treat non-alcoholic fatty liver disease [11]. It also has antioxidant and immunomodulatory properties [11][12][13][14]. Current research on diosgenin has shown that it possesses anticancer properties by inducing differentiation of human erythroleukemia cells through changes in lipoxygenase activities [15], promoting cell cycle arrest [16], and targeting several molecules involved in inhibiting cell proliferation, invasion, migration, angiogenesis, and metastasis of various types of human cancer [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…The examination uncovered methanol and luid concentrates at a portion of 200 mg/kg body weight switched diabetes initiated hyperlipidemia.] Alcoholic concentrate of the C. igneus at the portion of 400 mg/kg (p.o) had altogether diminished the degrees of triglycerides, cholesterol, Low-Density Lipoprotein levels in Triton prompted hyperlipidemic rats (Selim and Jaouni, 2016;Shanmugavadivu and Velmurugan, 2018).…”
Section: Resultsmentioning
confidence: 98%